2007
DOI: 10.1113/jphysiol.2007.145649
|View full text |Cite
|
Sign up to set email alerts
|

TRESK two‐pore‐domain K+ channels constitute a significant component of background potassium currents in murine dorsal root ganglion neurones

Abstract: TRESK (TWIK-related spinal cord K + channel) is the most recently identified member of the two-pore-domain potassium channel (K 2P ) family, the molecular source of background potassium currents. Human TRESK channels are not affected by external acidification. However, the mouse orthologue displays moderate pH dependence isolated to a single histidine residue adjacent to the GYG selectivity filter. In the human protein, sequence substitution of tyrosine by histidine at this critical position generated a mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
185
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(214 citation statements)
references
References 50 publications
26
185
3
Order By: Relevance
“…Indeed, among sanshool-sensitive KCNK subtypes, KCNK18 contributes significantly to the background K + current in cultured DRG neurons 20 . Moreover, in situ hybridization histochemistry suggests that KCNK18 transcripts are expressed by a significant fraction of primary sensory neurons 21 . However, this analysis is likely to overestimate the prevalence of KCNK18 expression because of the high sequence conservation among KCNK subtypes, with consequent hybridization of in situ probes to numerous KCNK transcripts.…”
Section: Sanshool Sensitivity Correlates With Kcnk Subtype Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, among sanshool-sensitive KCNK subtypes, KCNK18 contributes significantly to the background K + current in cultured DRG neurons 20 . Moreover, in situ hybridization histochemistry suggests that KCNK18 transcripts are expressed by a significant fraction of primary sensory neurons 21 . However, this analysis is likely to overestimate the prevalence of KCNK18 expression because of the high sequence conservation among KCNK subtypes, with consequent hybridization of in situ probes to numerous KCNK transcripts.…”
Section: Sanshool Sensitivity Correlates With Kcnk Subtype Expressionmentioning
confidence: 99%
“…Thus, we conclude that KCNK channels are the likely targets of sanshool action. Indeed, members of this two-pore K + channel subfamily (KCNK2, KCNK3, KCNK9, KCNK10 and KCNK18) have been proposed to set the resting membrane potential of primary afferent sensory neurons, with KCNK18 (TRESK) having the predominant role [19][20][21] .…”
Section: Sanshool Inhibits a Ph-sensitive K + Leak Conductancementioning
confidence: 99%
“…The first is TREK2, which may well contribute Ͼ10 mV (above). Other candidates are other K2Ps (TRESK is in all sizes of DRG neurons) (Dobler et al, 2007;Yoo et al, 2009), Cl Ϫ channels (Mayer, 1985), and voltage-dependent K ϩ currents (such as Kv7.2/7.5 or K ATP ). The last group were reported to contribute very little (Ͻ1.3%) normally to the resting K ϩ -standing current at 37°C (Kang and Kim, 2006), although their contribution would increase with greater depolarization.…”
Section: Extent Of Em Dependence On Trek2mentioning
confidence: 99%
“…Cl Ϫ channels and voltage-sensitive K ϩ channels (e.g., M-current and/or K ATP ) may contribute to their Ems (Kawano et al, 2009;Rose et al, 2011). However, Kang and Kim (2006) showed that at 37°C TREK2 contributed ϳ69% of the K ϩ standing current (responsible for the majority of Em) in a third of small-sized cultured neonatal rat DRG neurons; TRESK, expressed in all sizes of DRG neurons (Dobler et al, 2007), contributed 16% and TREK1 12%. The relatively high TREK2 mRNA in rat DRGs (Marsh et al, 2012) supports TREK2 contributing substantially to Em in adult DRG neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of TRESK in DRG neurons attenuates nerve injury-induced mechanical allodynia (68). The TRESK channel presents perhaps the best opportunity for development of antimigraine therapeutics, given its predicted role in controlling neuronal excitability (69).…”
Section: Othersmentioning
confidence: 99%